الحياة الاجتماعية للجزائر العثمانية من خلال الكتابات الأجنبية جيمس كاثكارت ووليام شالر1785_1824م (أنموذجا) - بوعرقوب مريم (My University, 2025)
Summary : This study focuses on the social life in Ottoman Algeria through the writings of foreigners, specifically James Leander Cathcart (1785-1796) and William Shaler (1816-1824). The research is structured into three chapters. The first chapter delves into the biographies of James Leander Cathcart and William Shaler. The second chapter discusses the demographic and social situation of Algiers as depicted by these authors. Finally, the third chapter examines the living conditions of Algiers' inhabitants through their accounts. Among the key findings of this study is that both James Leander Cathcart and William Shaler arrived in Algeria under different circumstances. Initially, James Leander Cathcart was a captive after an American ship was seized in 1785, later becoming a scribe for the Dey of Algiers. William Shaler, on the other hand, came to Algeria to negotiate a peace treaty with the Dey and was subsequently appointed as the United States Consul in Algiers in 1816. Despite their differing reasons for being in Algeria, both men shared a keen observational eye and a strong interest in the details of Algiers during their stay. They meticulously documented everything they saw and heard in their memoirs, which serve as an invaluable historical source for understanding life in Algeria during the Ottoman era. ---------------------------- الملخص: تتمحور الدراسة حول الحياه الاجتماعية للجزائر العثمانية من خلال كتابات الأجنبية جيمس ليندر كاثكارت1785, 1796 ويليام شالر( 1816 1824 م)وقد تركزت هذه الدراسة على ثلاث فصول حيث تم التطرق في الفصل الاول الى بيوغرافية جيمس ليندر كاثكارت ووليام شالر، اما الفصل الثاني تم التحدث فيه عن الوضع الديموغرافي والاجتماعي لمدينه الجزائر من خلال المؤلفين وبالنسبة لفصل الثالث فقد تم التحدث عن الوضع المعيشي لسكان مدينه الجزائر من خلال المؤلفين ومن بين النتائج المتواصلة اليها في هذه الدراسة أن كلًا من جيمس ليندر كاثكارت وويليام شالر جاءا إلى الجزائر لأسباب مختلفة. ففي البداية، كان جيمس ليند كاثكارت أسيرًا بعد الاستيلاء على سفينة أمريكية عام 1785، ليصبح لاحقًا كاتبًا لدى داي الجزائر. أما ويليام شالر فقد قدم إلى الجزائر لإبرام صلح مع الداي، وتم تعيينه لاحقًا قنصلًا للولايات المتحدة في الجزائر عام 1816. على الرغم من اختلاف ظروف قدومهما، تشاركا في ملاحظتهما الدقيقة واهتمامهما بتفاصيل مدينة الجزائر خلال فترة إقامتهما. فقد دوّنا كل ما رأوه وسمعوه في مذكراتهما، والتي تُعد مصدرًا تاريخيًا قيمًا لفهم الحياة في الجزائر خلال العهد العثماني. ------------------------------ Résume : L’étude s’articule autour de la vie sociale de l’Algérie ottomane à travers les écrits d’étrangers James Leander Cathcart (1785, 1796 William Schaller (1816-1824 après J.-C.). Cette étude s’est concentrée sur trois chapitres, où le premier chapitre traitait de la biographie de James Leander Cathcart et William Schaller. Quant au deuxième chapitre, la situation démographique et sociale de la ville d’Alger a été abordée à travers les auteurs. Quant au troisième chapitre, la situation de vie des habitants de la ville d’Alger a été discutée par les auteurs. Parmi les résultats continus de cette étude, il y a le fait que James Leander Cathcart et William Schaller sont venus en Algérie pour des raisons différentes. Initialement, James Lynde Cathcart a été capturé après la capture d’un navire américain en 1785, devenant plus tard clerc du Dey d’Alger. Quant à William Shaler, il est venu en Algérie pour conclure la paix avec le Dey, et a ensuite été nommé consul américain en Algérie en 1816. Malgré les différentes circonstances de leur arrivée, ils ont partagé une observation attentive et une attention aux détails de la ville d’Alger pendant leur séjour. Ils ont enregistré tout ce qu’ils ont vu et entendu dans leurs mémoires, qui sont une source historique précieuse pour comprendre la vie en Algérie pendant l’époque ottomane.
Keywords: كاثكارت، شالر، الحياة الاجتماعية، مدينة الجزائر.